Changes in Ecological and Economic Conditions of Sero Fishermen After Reclamation in Kamal Muara, North Jakarta - Dewi Susiloningtyas; Shasa Chairunnisa; Titin Siswantining; Tuty Handayani (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Reclamation in Kamal Muara North Jakarta changes the surrounding fishery activities. It is estimated that there are changes in the ecological and economic conditions of fishermen. This study aims to analyze the ecological and economic changes that occur in Sero fishermen in Kamal Muara after the reclamation of artificial islands. This research uses a descriptive quantitative approach with a questionnaire, observation, interview, and documentation methods. The results showed that after reclamation, the fishing ground of Sero fishermen moved along the Dadap coast, Tangerang with a distance of less than one nautical mile from the coastline. In addition to fishing ground changes, the results of the paired sample t-test on the catches volume and profit of Sero fishermen showed significant changes after the reclamation of the artificial island. However, operational costs did not show any significant changes between before and after reclamation. This study concludes that there are changes in the ecological and economic conditions of Sero fishermen in Kamal Muara after the reclamation.